Content Analysis of Social Studies Textbooks for Middle School in Relation to Legal Education and Suggestions for Inclusion - Al-Janabi, Muna Mohammed Maki Asal; Al-Ajirash, Prof. DR. Haider Hatem Faleh; Salman, Asst. Prof. liqaa Mahdi (South Eastern European Journal of Public Health, 2024)
This study aims at identifying “Content Analysis of Social Studies Textbooks for Middle School in Relation to Legal Education and Suggestions for Inclusion”. The study community involved the content of social studies books for the intermediate stage for the first intermediate Stage for the year (2019) Social Studies (3rd edition) which is taught in the academic year (2023-2024 AD), and for the second intermediate Stage for the year (2023 AD) (4th edition) which is taught in the academic year (2023-2024 AD), and for the third intermediate Stage for the year (2023 AD) (2nd edition) which is taught in the academic year (2023-2024 AD), and the researcher excluded (the introduction, the index, and the questions), and the number of pages subject to analysis became (389) pages. The research sample contained analyzing the content of social studies books for the intermediate stage, and the total analysis pages were (432) activities, as the number of analysis pages for the social studies book for the first intermediate Stage was (119) pages, for the second intermediate grade it was (126) pages, and for the third intermediate Stage it was (144) pages. "To achieve the goal" of the research, with regard to legal education, the researcher prepared the analysis tool (questionnaire) for analyzing the content of social studies books for the intermediate stage for legal education, which amounted to (39) concepts after reviewing the literature and previous studies, then it was presented to experts to express their opinions and observations on it, and in light of that, some paragraphs were deleted, added and modified, and by relying on the modified tool to analyze the content of social studies books according to legal education and to ensure the stability of the analysis of legal education, the researcher used the analysis with the help of other analysts and using the Holsti equation for legal education. The stability coefficient between the researcher and the first analyst was (89%) and the stability coefficient between the researcher and the second analyst was (90%). The researcher analyzed the content again with a time difference between the two analyses (30 ) Days and the stability coefficient between the two analyses reached (92%) and the topic or idea unit was used as units of analysis because it is appropriate for the research objective and the nature of the analyzed content and the analysis was carried out according to fixed steps and foundations, and for the purpose of extracting the results the researcher used repetitions and percentages for legal education, and among the most important conclusions that the researcher reached: 1- The content of the social studies books for the first, second and third Stages did not reflect legal education in an equal and balanced manner. 2- Lack of emphasis on the following legal education concepts: (organ trafficking, anti-smoking, anti-drug and psychotropic drugs) The researcher recommended a set of recommendations and proposals, including: Reviewing the content of the social studies books in a way that ensures the provision of all legal education concepts within 39 concepts. The researcher suggested the following : 1- Conducting a study similar to the current study on other educational stages in the social studies books for the intermediate stage. 2- Conducting an analytical study that helps to identify the difficulty that hinders the provision of legal education paragraphs within the content of the social studies books for the intermediate stage.